The G2A Receptor Deficiency Aggravates Atherosclerosis in Rats by Regulating Macrophages and Lipid Metabolism - Cui, Xueqin; Xing, Roumei; Tian, Yue; Wang, Man; Sun, Yue; Xu, Yongqian; Yang, Yiqing; Zhao, Yongliang; Xie, Ling; Xiao, Yufang; Li, Dali; Zheng, Biao; et al. (Frontiers in Physiology, 2021)
The orphan G protein-coupled receptor G2A has been linked to atherosclerosis development. However, available data from mice models are controversial. Rat G2A receptor bears more similarities with its human homolog. We proposed that the atherosclerosis model established from Ldlr-/- rat, which has been reported to share more similar phenotypes with the human disease, may help to further understand this lipid receptor. G2A deletion was found markedly aggravated lipid disorder in the rat model, which has not been reported in mice studies. Examination of aortas revealed exacerbated atherosclerotic plaques in G2A deficient rats, together with increased oxidative stress and macrophage accumulation. In addition, consistently promoted migration and apoptosis were noticed in G2A deficient macrophages, even in macrophages from G2A single knockout rats. Further analysis found significantly declined phosphorylation of PI3 kinase (PI3K) and AKT, together with reduced downstream genes Bcl2 and Bcl-xl, suggesting possible involvement of PI3K/AKT pathway in G2A regulation to macrophage apoptosis. These data indicate that G2A modulates atherosclerosis by regulating lipid metabolism and macrophage migration and apoptosis. Our study provides a new understanding of the role of G2A in atherosclerosis, supporting it as a potential therapeutic target.